The Migration of Constitutional Ideas - Choudhry, Sujit (Cambridge University Press, 2013)
Usually judges ask the questions, but on this night the roles were reversed. The occasion was a public conversation between United States Supreme Court Justices Breyer and Scalia, answering questions posed by constitutional scholar Norman Dorsen.1 The topic was the ‘Constitutional Relevance of Foreign Court Decisions’ to the Court’s constitutional case law. For a court routinely called upon to address the most divisive issues in US public life, judicial citation practices hardly seem worthy of a rare evening with two of its most distinguished members. Yet the auditorium was packed, with hundreds more watching over a live video feed.